Strengthening Islamic Financial Literacy and Fintech Investment for Diaspora in Turkey - Praswati, Aflit Nuryulia; Rahmatdi; Nandya Octanti Pusparini; Nurul Latifatul Inayati; Arief Dwi Saputra,; Syaban Al Musyaffa Ibnu Ahmad (Abdi Psikonomi, 2025)
The Indonesian diaspora in Turkey, particularly students and migrant workers, continues to face challenges in Islamic financial literacy as well as limited access to information on investment opportunities in Indonesia through financial technology (fintech). Such conditions may hinder optimal financial management. To address these issues, this community engagement program was designed to equip the diaspora with an understanding of Islamic financial principles and provide education on investment opportunities through fintech platforms, both sharia-based and conventional. The activities were conducted through interactive seminars, discussions, and mentoring sessions delivered in both online and offline formats, in collaboration with PCIM Turkey, the PPI Turkey community, and Gelin as strategic partners. The program adopted a multidisciplinary approach by involving lecturers from the Faculty of Islamic Studies to deliver counseling on sharia aspects of investment. The implementation stages included program planning, partner coordination, site surveys, seminars, and evaluation through pre-tests and post-tests. The evaluation results demonstrated an increase in participants’ understanding of Islamic financial literacy and fintech utilization. Program documentation was disseminated through social media, the UMS news portal, and the Muhammadiyah news portal, while a social media group was established as a sustainable channel for communication and follow-up mentoring.